Effect of Occlusal Reduction on Postoperative Pain in Teeth with Irreversible Pulpitis and Mild Tenderness to Percussion - Ghimire, Siddharth; Dixit, Punam Basnet; Roy, Deepak Kumar; Dhital, Sweta; Dahal, Sirjana (Journal of College of Medical Sciences-Nepal, 2020)
Background: One of the most important aspects during endodontic treatment is to control pain during and after root canal treatment. Occlusal reduction has been widely used after root canal treatment to reduce post treatment pain and flare up. The purpose of this study was to evaluate the effect of occlusal reduction on postoperative pain in teeth with irreversible pulpitis and tenderness to percussion. Methods: Forty-eight patients with irreversible pulpitis and mild tenderness to percussion were allocated into two groups; occlusal tooth reduction group and no occlusal tooth reduction group. After root canal instrumentation, patients were recalled after 24 hours, 2nd day, 3rd day, 4th day, 5th day and 6th day to record their postoperative pain on the Visual Analogue Scale. The final outcome that is mean post instrumentation pain score was measured till 6 days of post instrumentation. Data was collected and entered in Microsoft Excel sheet and analysis was done using Statistical Package of Social Sciences software version 20. Results: There was no significant difference in postoperative pain between the 2 groups (P > .05) after root canal preparation. Conclusions: Occlusal surface reduction did not provide any further reduction in postoperative pain for teeth with irreversible pulpitis and mild tenderness to percussion compared with no occlusal reduction. Keywords: endodontic preparation; occlusal reduction; postoperative pain; root canal treatment.